Towards Solving the Riddle of Forgetting in Functional Amnesia: Recent Advances and Current Opinions - Staniloiu, Angelica; Markowitsch, Hans J. (Frontiers in Psychology, 2012)
Remembering the past is a core feature of human beings, enabling them to maintain a sense of wholeness and identity and preparing them for the demands of the future. Forgetting operates in a dynamic neural connection with remembering, allowing the elimination of unnecessary or irrelevant information overload and decreasing interference. Stress and traumatic experiences could affect this connection, resulting in memory disturbances, such as functional amnesia. An overview of clinical, epidemiological, neuropsychological and neurobiological aspects of functional amnesia is presented, by preponderantly resorting to own data from patients with functional amnesia. Patients were investigated medically, neuropsychologically and neuroradiologically. A detailed report of a new case is included to illustrate the challenges posed by making an accurate differential diagnosis of functional amnesia, a condition that may encroach on the boundaries between psychiatry and neurology. Several mechanisms may play a role in “forgetting” in functional amnesia, such as retrieval impairments, consolidating defects, motivated forgetting, deficits in binding and reassembling details of the past, deficits in establishing a first person autonoetic connection with personal events and loss of information. In a substantial number of patients, we observed a synchronization abnormality between a frontal lobe system, important for autonoetic consciousness, and a temporo-amygdalar system, important for evaluation and emotions, which provides empirical support for an underlying mechanism of dissociation (a failure of integration between cognition and emotion). This observation suggests a mnestic blockade in functional amnesia that is triggered by psychological or environmental stress and is underpinned by a stress hormone mediated synchronization abnormality during retrieval between processing of affect-laden events and fact-processing.